Profile of Scientific Attitude of Elementary School Students in RADEC Model Science Learning with the Water Theme - Jaenudin, Irfan; Syaodih, Ernawulan; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
Scientific attitude is a component that is less attention in science learning in elementary schools and its mastery is still in the low category. This study aims to describe the profile of the scientific attitude of students who learn science by using the RADEC model in the theme of water in elementary schools. This study uses a quantitative descriptive research design with the research subjects were fifth grade of elementary school students. The data collection instrument used in this study was in the form of a scientific attitude questionnaire given to students to find out the scientific attitude profile of students who participated in science learning by using the RADEC model. The results of this study indicated that the profile of students' scientific attitude for curiosity aspect was 74%, the aspect critical thinking attitude was 76%, the aspects of open minded and cooperation were 83%, and the aspects of discovery and creativity were 71%. The average percentage of students' scientific attitude profile in this study for all aspects was 76% or in the good category. It can be concluded that the scientific attitude of students after participating in the RADEC model in learning science had increased and was included in the good category.